Isolation and Characterization of Local Isolates of Rhizobia in Nineveh Governorate/Iraq - Ahmed Mohammed; Raad Sultan (College of Education for Pure Sciences, 2021)
In this study, thirty-six local isolates of rhizobial bacteria were isolated from root nodes of different leguminous plants collected from different areas in Nineveh Governorate/Iraq. The rhizobial colonies were purified and their agronomic and biochemical characteristics were studied. Results of this study showed that the local isolates had the ability to consume different sugars as a carbon source. Also, the antibiotic sensitivity test showed that only one isolate, Rhizobium leguminosarum bv. phaseoli AS12 was resistant to the antibiotic Azithromycin 15 µg/ml, and the isolate Rhizobium leguminosarum bv. phaseoli AS14 showed resistance to the antibiotic Gentamycin 10 µg/ml, and the rest of the isolates showed different rates of resistance and sensitivity for the rest of the antibiotics. The local isolates showed different NaCl tolerance levels up to 8.0 %, while no tolerance was observed for Rhizobium leguminosarum bv. viciae AS11 isolate at any of the studied concentrations. Results of heavy metal salt tolerance study showed that the isolates of Ensifer meliloti AS34 and Rhizobium leguminosarum bv. viciae AS36 were sensitive to ZnSo4 at a concentration of 25 µg/ml, while the tolerability of the other isolates to the studied heavy salts differed at concentrations higher than 25 µg /ml. All the studied isolates showed a positive result in staining with Congo red and Aniline blue dyes. Maximum exopolysaccharide production was 494 mg/Li by Rhizobium leguminosarum bv. viciae AS35. Antimicrobial activity test showed maximum inhibition zone 17 mm by Rhizobium leguminosarum bv. viciae AS36 against Proteus vulgaris.